Production of mother oysters of Pinctada fucata(Gould) by manipulation of stocking density - I, Jagadis; Ignatius, Boby; Victor, A C C; Ilangovan, K (Indian Journal of Fisheries, 2014)
Marine pearl culture is a multifaceted technique involving three different kindof works namely i) seed production, ii) farming and mother oyster developmentand iii) nucleation and pearl production. To make the technique more viableand economically feasible it is imperative to make critical analysis of the varioustechnicalities involved in the culture strategy.Â Hence a commercial level schemeon marine pearl culture in the inshore waters of Gulf of Mannar (GOM) wastaken up during 1998-2004 at Mandapam Regional Centre of Central MarineFisheries Research Institute (CMFRI). Critical analysis of the data revealedthat a definite upgradation of pearl culture technology is required in manycomponents coupled with policy decisions by the State Government.Â The presentpaper focuses on a single major problem of production of mother oysters fornucleation and pearl production on a continuous and commercial scale ofoperation. The culture method, appropriate farm management, stock density,growth and survival, culling and their effect on the production of mother oyster suitable for nucleation are presented in the paper.